Symptomatic overlap in overactive bladder and interstitial cystitis/bladder pain syndrome: development of a new algorithm. (24th October 2018) - Ackerman, A. Lenore; Lai, H. Henry; Parameshwar, Pooja S.; Eilber, Karyn S.; Anger, Jennifer T.
Abstract : Objectives: To address challenges in the diagnosis and classification of storage lower urinary tract symptoms (LUTS), we sought to define the fundamental features of overactive bladder (OAB) and interstitial cystitis/bladder pain syndrome (IC/BPS), two conditions with considerable symptomatic overlap. Through retrospective comparison of self‐reported symptoms in women with a range of clinical presentations and symptom severities, we have attempted to refine the diagnostic features of OAB and IC/BPS and to develop a novel clinical nomogram to improve patient screening and classification. Materials and Methods: We performed a univariate analysis comparing responses to the female Genitourinary Pain Index (fGUPI), the OAB Questionnaire and O'Leary–Sant Indices (the Interstitial Cystitis Symptom Index and Interstitial Cystitis Problem Index) in an initial cohort of 50 patients with OAB, patients with IC/BPS and control subjects. Only eight questions differed significantly between the IC/BPS and OAB groups; we used five unique questions and three measuring bother to generate a novel composite scoring system and nomogram that included urgency incontinence, bladder pain and symptomatic bother domains to differentiate these populations, which was validated in a second cohort of 150 patients. The addition of a self‐reported bother index resulted in the creation of a diagnostic algorithm to identify and classify LUTS clusters across the total population. Results: While all validated questionnaires could distinguish between controls and patients with storage LUTS, no combined symptom scores differed significantly between the IC/BPS and OAB groups. These results are reflective of the prevalence of significant bladder pain (35%) in patients with OAB and the presence of urge incontinence (25%) in patients with IC/BPS. Only the fGUPI pain domain scores differed between patients in the OAB and IC/BPS groups, but it was not accurate enough for diagnostic evaluation (68% accuracy). Our composite scores and nomogram gave a much‐improved diagnostic accuracy (94%) and demonstrated utility as a screening tool to identify storage LUTS in patients presenting for unrelated complaints, e.g. microhaematuria. Conclusions: There is significant overlap of urinary tract symptoms between OAB and IC/BPS. We present a novel algorithm that provides a binary output capable of guiding clinical diagnosis. Future studies aimed at assessing the diagnostic value of novel classification schemes that address symptoms rather than specific diagnoses may improve patient prognosis.